Alveolar defects before and after surgically assisted rapid palatal expansion (SARPE): a CBCT assessment - ROMANO,Fábio Lourenço (2022)
ABSTRACT Introduction: Surgically Assisted Rapid Palatal Expansion (SARPE) promote maxillary expansion in skeletally mature patients. This technique is effective; however, some side effects are still unknown. Objectives: evaluate the presence of alveolar defects (dehiscences and fenestrations) in patients submitted to the SARPE. The null hypothesis tested was: SARPE does not influence the number of dehiscences and fenestrationss. Methods: A retrospective quasi-experiment study of a convenience sample of 279 maxillary teeth, in 29 patients evaluated with Cone Beam Computed Tomography (CBCT) at T1 (before SARPE), T2 (after expansion) and T3 (after retention), was performed. The examined teeth were: canines, first and second premolars, first and second molars. in axial, coronal, and cross-sectional views. The evaluations involved viewing slices from mesial to distal of the buccal roots. Results: All statistical analyses were performed using SAS 9.3 and SUDAAN softwares. Alpha used in the study was 0.05. Alveolar defects increased statistically from T1 (69.0%) to T2 (96.5%) and T3 (100%). Dehiscences increased 195% (Relative Risk 2.95) at the end of expansion (T2). After retention (T3), individuals were on average 4.34 times more likely to develop dehiscences (334% increase). Fenestrations did not increase from T1 to T2 (p = 0.0162, 7.9%) and decreased from T2 to T3 (p = 0.0259, 4.3%). Presence of fenestrations at T1 was a significant predictor for the development of dehiscences in T2 and T3. Dehiscences increased significantly in all teeth, except second molars. Conclusion: The null hypothesis was rejected. After SARPE the number of dehiscences increased and fenestrations decreased. Previous alveolar defects were predictor for dehiscences after SARPE.